RANCANG BANGUN PENGENDALI LAMPU DENGAN KOMUNIKASI SERIAL BERBASIS MIKROKONTROLLER PIC16F877 DAN 16F876 MELALUI JARINGAN LISTRIK RUMAH - Irsyam, Muhammad; Algusri, Missyamsu; Suhermanto, Suhermanto (SIGMA TEKNIKA, 2024)
Serial data transmission can be applied by the use of the grid as a carrier is one alternative that has some advantages, such as reducing the use of cables In this design project created a special application of serial data communication via the electricity network that uses circuit PIC16F877di Microcontroller Master controller as the main controller to control ON / OFF to 5 pieces Slave controller circuit using the PIC16F876 microcontroller to control the lights as the electrical load. Research conducted using a modulation method Frequency Shift Keying (FSK) as modulator and demodulator, also using a series transformer coupling and high pass filter circuit. The main component Frequency Shift Keying (FSK) the Integrated Circuit (IC) XR2206 as a Modulator and Demodulator IC XR2211 as, as well as using a passive filter that serves to pass a predetermined frequency is 70KHz - 80KHz. The frequency value to be achieved by calculating the value of an external capacitor and resistor. The results of the calculations at the design stage modulator, with a value of C = 10nF obtained value R1 = 1428Ω, R2 = 1250Ω. Keywords: PIC16F877, PIC16F876, XR2206, XR2211